Application of Project-Based Learning approach in teaching speaking to 11th form students: An action research project at a High School in Thai Binh = Áp dụng phương pháp học theo dự án trong việc dạy kỹ năng nói cho học sinh lớp 11: Nghiên cứu - Bùi, Thị Huệ (2019)
This study is carried out to examine how Project-Based Learning affects students‘ speaking skills as well as students‘ opinions on Project-Based Learning implementation. The study adopts action research with the use of both quantitative and qualitative data collection methods, including pre- and post – tests, questionnaire, teaching journals and interviews. The findings report that the students in the study made some significant improvement in their speaking scores.